Development of a quantitative microbial risk assessment model for foodborne Campylobacter infection - Premarathne, Jayasekara Mudiyanselage Krishanthi Jayarukshi Kumari; Tang, John Yew Huat; Basri, Dayang Fredalina; Rukayadi, Yaya; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Campylobacterspecies are one of the important foodborne pathogens in the world. Risk assessment is a scientific approach for estimating and evaluating potential adverse effects on human with resulting from exposure to hazards. A microbiological risk assessment was conducted to assess the health risk associated with consumption of chicken meat contaminated with Campylobacter in Malaysia. The risk assessment model was developed based on the framework proposed by the Codex Alimentarius Commission with simulating the contamination of chicken with Campylobacter from retail to table continuum. Available published data was incorporated into the model for estimation of the associated risk. The risk assessment model was created using @RISK software. Monte Carlo assessment was used to calculate the risk of Campylobateriosis associated with the consumption of chicken. According to the simulation analysis, the probability of contamination of chicken with Campylobacter spp. was 82.29 %. The model predicted that risk of illness due to undercooked chicken was 94.40 per 100, 000 population per year. Findings of this study will aid to identify the appropriate effective risk mitigation strategies in eliminating Campylobacter from poultry.